2013
DOI: 10.1049/iet-smt.2012.0157
|View full text |Cite
|
Sign up to set email alerts
|

Design, development and evaluation of optical motion‐tracking system based on active white light markers

Abstract: The precise measurement and analysis of human movements is an essential step in biomechanical research used in sports or medicine. Measurement systems used for motion tracking should be non-invasive, safe to use, widely customisable and cost-efficient. In this study, complete design, development and evaluation of a high-speed optical motion tracking and analysis system is described. The system aims to analyse movements for sports and medical applications. The novelty of the proposed system is its design, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…We designed an optical motion-tracking system based on active white light markers [24] and showed that it could be used as an efficient tool for measuring kinematic data on human motion. We also developed a structured light 3D scanner for estimation of human anthropometric parameters [25].…”
Section: Introductionmentioning
confidence: 99%
“…We designed an optical motion-tracking system based on active white light markers [24] and showed that it could be used as an efficient tool for measuring kinematic data on human motion. We also developed a structured light 3D scanner for estimation of human anthropometric parameters [25].…”
Section: Introductionmentioning
confidence: 99%
“…One can conclude that the system's depth reconstruction performs with a mean error of 1.5 mm and an RMSE better than 1 cm, which is more than adequate for its intended application. The accuracy of the proposed system could be improved by implementing a sub-pixel point center detection algorithm (Ling, 2005;Stancic, Grujic, 2013), while including more points in the projected pattern would increase the system's final resolution. To summarize, the only difference between the partial and full scans is the number of points projected onto the area, and thus, the resolution of the scan is different.…”
Section: Resultsmentioning
confidence: 99%
“…The radius of the marker is 10 pixels, which is 10% of the amplitude of movement. The frame rate is 25 frames/s, and the simulated time of exposure is 1/30 s. The decrease in the amplitude is compared with the theoretical one, assuming a point-like marker described in (12). A sine wave is fitted to the estimated center points with four-parameter sine fitting algorithm [17].…”
Section: A Sinusoidal Movement: Marker Has Finite Dimensionmentioning
confidence: 99%
“…In [12], the Gaussian marker model is used to describe the partial coverage of the pixel by the marker. The intensity distribution is assumed to be…”
Section: ) Fitting Gaussian Marker Modelmentioning
confidence: 99%
See 1 more Smart Citation